2021
DOI: 10.3390/cancers13040831
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK Inhibition Mitigates Hypoxia-Induced AR Signaling in Castration-Resistant Prostate Cancer

Abstract: Background: Aberrant androgen receptor (AR) signaling is a major driver of castration-resistant prostate cancer (CRPC). Tumor hypoxia increases AR signaling and is associated with treatment resistance in prostate cancer. Heat shock protein 27 (Hsp27) is a molecular chaperone that is activated in response to heat shock and hypoxia. Hsp27 has previously been reported to facilitate AR nuclear translocation in a p38 mitogen-activated protein kinase (MAPK) dependent manner in castration-sensitive prostate cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…However, it was also found that both GSE16561 and GSE100927 were enriched in MAPK, Cytokine-cytokine receptor interaction, antigen processing and presentation, and cGMP-PKG signaling pathways. MAPK pathway is implicated in various cellular activities including cell apoptosis and inflammation [ 23 , 24 ]. Abnormally activated MAPK pathways serve as a major role in the development of multiple inflammations, and targeting MAPK pathways have been proved to effectively alleviate the symptom of atherosclerosis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it was also found that both GSE16561 and GSE100927 were enriched in MAPK, Cytokine-cytokine receptor interaction, antigen processing and presentation, and cGMP-PKG signaling pathways. MAPK pathway is implicated in various cellular activities including cell apoptosis and inflammation [ 23 , 24 ]. Abnormally activated MAPK pathways serve as a major role in the development of multiple inflammations, and targeting MAPK pathways have been proved to effectively alleviate the symptom of atherosclerosis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 can also activate p38 MAPK signalling independent of androgen, which by this mechanism would increase AR signalling [87]. Inhibition of p38 MAPK signalling decreased proliferation in AR-positive cell lines in normoxia, and growth was further compromised by hypoxia, which is another trigger for p38 MAPK activation [88].…”
Section: Mitogen-activated Protein Kinase Pathwaymentioning
confidence: 99%
“…During ADT, the genomic repression of the p38 MAPK pathway would be ablated and reversed. One of the results would be increased hsp27, which would be predicted to increase stability and nuclear translocation of the AR [87,88], as well as enhance survival via the p38 MAPK pathway [88]. Activation of the p38 MAPK pathway has also been linked to epithelial-mesenchymal transition (EMT) and metastasis [88,168].…”
Section: P38 Mapkmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the in vivo growth of ovarian cancer cells is hampered by CDKN2B-AS1 depletion [ 138 ] ( Figure 2 and Table 2 ). Hypoxia is known to activate p38, thus leading to cancer aggressiveness via enhancing cell survival [ 139 , 140 ]. Moreover, HIF-1α is activated by p38 [ 139 ].…”
Section: Lncrnas Regulating Hif-1α Expressionmentioning
confidence: 99%